A case-study on the small claims court in Malaysia / Rozlina Abu Bakar - Abu Bakar, Rozlina (Faculty of Law, 1987)
There has been a need for a long time for a court designated exclusively for civil claims involving relatively small sums of money. In some countries where small claims court or tribunals have been set up, they have generally served the public well and are useful to the other courts in dispensing off justice. January 2, 1987 was a starting point for Malaysia's first small claims court to commence in full session. Hence, this will be a good sign in disposing off the abundance of cases. Not only will it give justice to the public, by making the procedure less complicated, cheaper filing fees and speedy judicial remedy for the poor, as the saying goes, "Justice delayed is justice denied", but it needs no additional staff, less expenditure and eventually even lawyer's representation would be unnecessary. Other steps too, have been taken or envisaged to make things easy for the public, e.g. set forms for filing claims and informality of the court aura.